Peranan Alkitab Dalam Mendewasakan Manusia Dewasa - Ardianto silalahi; Damayanti Nababan (Publisher STPKat, 2022)
A topic that is often discussed but lacks understanding of the meaning of maturity, there is some spiritual maturity which is expressed in the teachings of Christians, that spiritual maturity is needed by Christians so that their lives really demonstrate the character of Christ. Spiritually mature believers will have firm faith in the midst of the onslaught of misleading teaching influences and amidst the various storms of life. Believers who experience spiritual maturity will have the desire to serve God faithfully so that many souls are brought to Christ. Therefore, the role of the Bible is very much needed in distinguishing true maturity from a Christian spiritual point of view.